If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -3) = m + 1 Reorder the terms: 2(-3 + m) = m + 1 (-3 * 2 + m * 2) = m + 1 (-6 + 2m) = m + 1 Reorder the terms: -6 + 2m = 1 + m Solving -6 + 2m = 1 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -6 + 2m + -1m = 1 + m + -1m Combine like terms: 2m + -1m = 1m -6 + 1m = 1 + m + -1m Combine like terms: m + -1m = 0 -6 + 1m = 1 + 0 -6 + 1m = 1 Add '6' to each side of the equation. -6 + 6 + 1m = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 1m = 1 + 6 1m = 1 + 6 Combine like terms: 1 + 6 = 7 1m = 7 Divide each side by '1'. m = 7 Simplifying m = 7
| 0.19y+0.09(y+4000)=1760 | | 2x^2-19x=154 | | -3-4x-5x=-66 | | 4/1/2=x | | 2x+20=100 | | 6t+1/6=t+7/12+t-5/12 | | X/4+2=6 | | 5(-6+4x)=50 | | 2r+d=100 | | x-3/5+3/5=-x/7 | | 3x^3-2x^2+147x-98=0 | | 1/4+1/2t=4 | | 96+b=-3b | | 8+6(-4p+8)=-64 | | 2x+4=342 | | 6=(-16t^2)+(30t)+5 | | 5(x+3)-(1+2x)=4x-1 | | 11x+6y=7000 | | 0.05x+0.10(160-x)=0.15x | | (9+2x)*5=6x+13 | | 15x-1=9x-19 | | 6(4x+8)=48 | | 10x+15=20x-2.5x | | 21/2+d=21/4 | | 2.5y+8=18 | | 12x-84=5x | | 8+3a=20 | | x^3-6x^2+10x-4=0 | | (9+2x)3=4(13) | | 80-d^2=0 | | 2a-7=25 | | (8c-3)-(5c)= |